2019
DOI: 10.1111/jcpt.12854
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant drug‐drug interactions and the risk for drug adverse effects among home‐dwelling older persons with and without type 2 diabetes

Abstract: What is known and objective Polypharmacy and age are known to increase the risk for potential drug interactions. Type 2 diabetes has been associated with polypharmacy and several comorbidities. Currently, there is no information on whether the frequency of clinically relevant drug‐drug interactions and the risk for drug adverse effects differ between older persons with and without diabetes. The aim of this study was to investigate the frequency of drug‐drug interactions and the risk for drug adverse effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
(38 reference statements)
2
4
1
2
Order By: Relevance
“…30 10.59% of the study cohort were found to have potentially serious clinically relevant DDIs, which is considered higher than previously reported (7.10%). 8 However, a direct comparison is unattainable due to the differences in comorbid conditions and medicines prescribed and different platforms used for assessing DDIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 10.59% of the study cohort were found to have potentially serious clinically relevant DDIs, which is considered higher than previously reported (7.10%). 8 However, a direct comparison is unattainable due to the differences in comorbid conditions and medicines prescribed and different platforms used for assessing DDIs.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Despite that, there is a paucity in addressing the risk of potential clinically relevant serious DDIs and PIMs. Only one study found that at least one potential serious clinically relevant DDIs was found (7.10%), 8 and two studies found that the prevalence of PIMs was found between (22.70%-68.10%). 9,10 Moreover, there is a lack of evidence on whether the presence of polypharmacy and its consequences can impact quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%
“…In three studies investigating Australian and American community-dwelling older persons and nursing home residents, 6-28% had been prescribed drugs which were either contraindicated or required dosage adjustments due to their kidney function [19][20][21]. In our previous study, one the most clinically relevant drug-drug interactions concerned NSAID and antihypertensives such as ACE-inhibitors, combination that has also increased risk of nephrotoxicity [30].…”
Section: Discussionmentioning
confidence: 96%
“…Estudios como el de Ibáñeza et al, realizado en España, reportaron en pacientes hospitalizados de un servicio de medicina interna, porcentajes de interacciones farmacológicas entre el 0.4 y 39 % en los pacientes medicados (14). Otros estudios han evaluado si esta incidencia podría estar relacionado con padecimientos crónicos como diabetes, no identificando alguna diferencia entre los grupos (44.5 % en pacientes con diabetes vs. 41.5 % en aquellos sin diabetes) al detectar al menos una interacción clínicamente importante (15). En nuestro estudio, el 47.…”
Section: Discussionunclassified